Measurement of the [xi]-b and [omega]-b baryon lifetimes - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2014)
Using a data sample of pp collisions corresponding to an integrated luminosity of 3 fb−1, the Ξb− and Ωb− baryons are reconstructed in the Ξb−→J/ψΞ− and Ωb−→J/ψΩ− decay modes and their lifetimes measured to beτ(Ξb−)=1.55−0.09+0.10 (stat)±0.03 (syst) ps,τ(Ωb−)=1.54−0.21+0.26 (stat)±0.05 (syst) ps. These are the most precise determinations to date. Both measurements are in good agreement with previous experimental results and with theoretical predictions.